Sockets, shellcode, porting & coding reverse engineering exploits and tool coding for security professionals - Foster, James C.; Price, Mike (Mike Morgan); McClure, Stuart (Rockland, MA : Syngress Pub. ; [Sebastopol, CA] : Distributed by O'Reilly Media in the United States and Canada, 2005)
Covers in detail the five most important disciplines for security professionals and software developers: coding, sockets, shellocode, porting applications, and coding security tools.
The book is logically divided into 5 main categories with each category representing a major skill set required by most security professionals: 1. Coding The ability to program and script is quickly becoming a mainstream requirement for just about everyone in the security industry. This section covers the basics in coding complemented with a slue of programming tips and tricks in C/C++, Java, Perl and NASL. 2. Sockets The technology that allows programs and scripts to communicate over a network is sockets. Even though the theory remains the same communication over TCP and UDP, sockets are implemented differently in nearly ever language. 3. Shellcode Shellcode, commonly defined as bytecode converted from Assembly, is utilized to execute commands on remote systems via direct memory access. 4. Porting Due to the differences between operating platforms and language implementations on those platforms, it is a common practice to modify an original body of code to work on a different platforms. This technique is known as porting and is incredible useful in the real world environments since it allows you to not recreate the wheel. 5. Coding Tools The culmination of the previous four sections, coding tools brings all of the techniques that you have learned to the forefront. With the background technologies and techniques you will now be able to code quick utilities that will not only make you more productive, they will arm you with an extremely valuable skill that will remain with you as long as you make the proper time and effort dedications. *Contains never before seen chapters on writing and automating exploits on windows systems with all-new exploits. *Perform zero-day exploit forensics by reverse engineering malicious code. *Provides working code and scripts in all of the most common programming languages for readers to use TODAY to defend their networks.
Security coding -- NASL scripting -- BSD sockets -- Windows sockets (Winsock) -- Java sockets -- Writing portable code -- Portable network programming -- Writing shellcode 1 -- Writing shellcode 2 -- Writing exploits 1 -- Writing exploits 2 -- Writing exploits 3 -- Writing security components -- Creating a Web security tool.
Keywords: Computer security -- Handbooks, manuals, etc; Programming languages (Electronic computers) -- Handbooks, manuals, etc; Electronic books; Handbooks, manuals, etc